Significados, cambios y contexto actual de trabajo. Estudio interpretativo (2012)
The present research illustrates how people are giving meaning to the contemporary socio-industrial changes, the new realities on the job organization, and its implications on the construction of the workers' subjectivity. The understanding of this meaning construction leads to the constitution of the individual as a psychological and a social process. The sample for the research is 28 workers from Bogotá, with whom interviews were conducted. The interviews were transcribed and interpreted using grounded theory. The results highlight the impact on technology, the legal standards, competition, ethical practices characteristic of the current socio labor spectrum and their incidence on the worker who is identified as available, competent and self-demanding at the moment the worker carries out a job.